Household energy and environmental analysis to highlight the impact of modern energy access in Bangladesh - Md. Shazib Uddin; S.K. Shamim Iqbal; Md. Imrul Kais Talukdar (Cogent Engineering, 2017)
Access of modern energy is the critical challenge in many developing countries to improve the socio-economic status and quality lifestyle. This paper illustrates the comparative energy and environmental analysis among three categories residential household in a developing country Bangladesh. The households are categorized based on types of energy access, since different communities adopted combination of different types of energy access. The aim of this study is to reflect the impacts of modern energy access and better combination the types of energy access in residential household to emphasize how to mitigate residential energy loss, reduce energy expenses, avoid limited fossil resources, reduce environmental impact, enhance modern facilities and improve the way of life. The study reveals that, household having combination of electricity access, metered gas connection and adoption of modern cooking appliances would be better option recommended in this study compared with other options.